Patient Safety Program in a Hospital with Reference to Costs Associated with Patient Falls (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Patient safety is an emerging field in healthcare that has indirectly or directly affected allstakeholders of healthcare delivery system in the last decade. World Health Organization guidelines foradverse event reporting and learning systems, 2005 describes adverse events as “an injury related to medicalmanagement in contrast to complications of disease.” These adverse events can be preventable or nonpreventable. Inpatient falls presents a serious challenge to the safety and quality of patients in hospitals.Falls are not harmless, they delays in functional recovery and prolonged hospitalization that can causepatients to suffer. The study was conducted to estimate the incidence and major reasons for falls. Methods:Retrospectively, case records from January 2016 to September 2018 of all the inpatients were researched forpatient fall incidents, reported to the committee. The committee findings noted and the costs were estimatedin terms of cost to the patients, and costs to the hospital. Results: 118 incidents of patient fall happenedin study period. 3(2.6%) of them experienced two or more falls during stay, 115 (97.4%) fell once.5 patients were morbidly obese. Costs to the hospital on each patient was Rs. 5412/-, not levied onpatients. Conclusion: The number of fall incidents and falls reporting system have been improved by earlydetection of reasons by conducting root cause analysis.
Keywords: Patient safety, Indian Patient falls, Obesity, Consciousness, Facilities Management.